Educação ambiental: representações sociais e práticas pedagógicas em cursos de formação de professores - Silva, Lucivânia Francini da (2014)
This research study focused on the preparation of environmental educators and, therefore, aimed to identify and analyze the relationships between social representations of environmental education and teaching practices developed by teachers of undergraduate courses in two federal universities, located in the southwest region of the Paraná. First the work was referenced with theoretical approach in which authors elucidate about the historical background of environmental education in Brazil, from its inception until its manifestation in Brazilian public policies; the fundamentals of environmental education in the conservative strand and critical stance, bringing an approach also about the issue of training of environmental educators in degrees. Following were treated the methodological procedures used in research, and discussed the relevance of the theory of social representations in studies on pedagogical practices of environmental education. Data were collected by means of questionnaires developed specifically for the study, one for teachers, consisting of identification issues, a matter of free recall by inducing termEnvironmental Education and essay questions in which subjects should justify induced evocations by the term inductor and write their conceptions of environmental education; and another for students of their teachers and courses surveyed, also composed of three parts, the first part of the identification, the second part consists of two issues free recall, whose terms were inducers Environment and Environmental Education and essay questions in which the subjects should justify induced by the respective inductors terms evocations. Also Political Pedagogical Project of undergraduate courses surveyed were analyzed. For analysis and discussion of the issues of free recall used the central core theory and essay questions for the techniques of content analysis and document analysis. The results indicated that teachers surveyed represent socially environmental education as a set of pedagogical practices whose purpose is the development of attitudes, values and behaviors in favor of environmental protection, with a view to sustainability, so that these social representations are directly related with their teaching environmental education, informed by themselves, or informed via reports of students. Showed up relations between the social representations of identified environmental education and the pedagogical practices of teachers surveyed.